Kontribusi Timor-Leste dalam Penegakan Hukum Laut Internasional: Studi Kasus Ratifikasi UNCLOS dan Perjanjian BBNJ - Arkan, Muhammad Hanif; Maharani, Nabilah Liztha (Media Hukum Indonesia (MHI), 2025)
This study examines Timor-Leste's contribution to the enforcement of international maritime law through its study of the ratification process of the United Nations Convention on the Law of the Sea (UNCLOS) and the Treaty on Biological Diversity Beyond National Jurisdiction (BBNJ). The background of this problem is rooted in the importance of international maritime law enforcement in maintaining order and justice at sea, as well as protecting valuable marine natural resources, especially for coastal and island states such as Timor-Leste. The purpose of this study is to evaluate the steps taken by Timor-Leste in fulfilling its international obligations and the impact of the ratification of UNCLOS and BBNJ on the country's national policies and international relations. This study uses a descriptive qualitative method with a case study approach. The results of the study indicate that Timor-Leste has been actively involved and taken significant steps in enforcing international maritime law, but still faces challenges in terms of resources and institutional capacity.